Preparation and application of catalyst for converting polystyrene foam plastic into benzoic acid through photocatalytic oxidation

Through photocatalytic technology, Pt/TiO2 and Pt-Au/TiO2 catalysts are used to oxidize and convert polystyrene foam into benzoic acid, solving the problem of recycling waste polystyrene foam and achieving efficient and environmentally friendly resource reuse.

CN119751237APending Publication Date: 2025-04-04INNER MONGOLIA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411849813.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recycle and utilize waste polystyrene foam plastics, and traditional recycling methods have problems of environmental pollution and resource waste.

Method used

Through photocatalytic technology, Pt/TiO2 and Pt-Au/TiO2 catalysts are used to oxidize and convert polystyrene foam into high-value benzoic acid to achieve resource reuse.

Benefits of technology

The efficient conversion of polystyrene foam to benzoic acid is achieved, with high yields, mild reaction conditions, low energy consumption and environmentally friendly.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Polystyrene (PS) is one of four general-purpose plastics, and along with continuous increase of the waste quantity, due to nondegradability, serious environment harm and white pollution, an efficient recovery and utilization technology needs to be developed urgently. The TiO2 material is cheap, easy to obtain, efficient, stable and environment-friendly, is widely applied to the field of photocatalysis, but has the problem of high photoinduced electron-hole pair recombination rate. The (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst is prepared through photo-reduction deposition of Pt and Au bimetal modified TiO2, has the characteristics of easily available raw materials, no toxicity and harmlessness, simple and feasible synthesis method, environmental friendliness and the like, is used for converting polystyrene foam plastic into benzoic acid through photo-catalytic oxidation, and is mild in reaction condition, low in energy consumption, environment-friendly and suitable for industrial production. According to the invention, hydrocarbon resources in polystyrene can be recycled and converted into benzoic acid with high added value, and the method has high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of a catalyst for photocatalytically oxidizing polystyrene foam plastics into benzoic acid. Background Art

[0002] Plastics have changed human society, bringing convenience, but due to their non-degradability, they seriously harm the environment and cause white pollution. At present, less than 10% of plastics can be recycled, and the rest are incinerated, piled up in landfills or scattered in the environment. There are three main technologies for the treatment and recycling of waste plastics: mechanical recycling, incineration and chemical recycling. Among them, chemical recycling can convert plastics as low-cost raw materials into high-value-added chemicals or fuels, and is considered to be a waste plastic treatment method with great economic and environmental benefits. For example, CN117402054A discloses a method for catalytically converting oxygen-containing waste plastics into benzoic acid monomers, wherein oxygen-containing waste plastics and 250mg CeO2 / Nb2O5 catalyst are dispersed in 100mL H2O2. When the temperature is 250℃ and the pressure is 6MPa, the yield of benzoic acid after 1h of reaction is 13%, and the yield of terephthalic acid is 37%. CN117185890A discloses a method for preparing a monoaromatic ring chemical raw material by thermal cracking of waste polystyrene. 0.5MPa of water vapor is introduced into a continuous reaction device. After reacting at 340°C for 30 minutes, the yield of styrene reaches 83.5%. Polystyrene (PS) is one of the four general-purpose plastics. With its own characteristics of light weight, firmness, corrosion resistance, and insulation, it is widely used in many fields such as foam packaging materials, building materials, disposable food containers, tableware, etc. With the continuous increase in the amount of waste polystyrene plastics, it is urgent to develop more efficient recycling and utilization technologies.

[0003] Photocatalysis is a green, environmentally friendly and energy-saving technology that converts solar energy into chemical energy. The application of this technology to catalyze the oxidation of polystyrene to benzoic acid not only has mild treatment conditions, low energy consumption and environmental friendliness, but also can recycle the hydrocarbon resources in polystyrene to generate high-value benzoic acid products. TiO2 materials are cheap, easy to obtain, efficient, stable and environmentally friendly, and are widely used in the field of photocatalysis. However, pure TiO2 has the problem of a high recombination rate of photoinduced electron-hole pairs. Therefore, it can be modified by precious metal deposition to improve its photocatalytic performance. Summary of the invention

[0004] The object of the present invention is to provide a preparation and application of a catalyst for photocatalytic oxidation of polystyrene foam plastics into benzoic acid.

[0005] The present invention provides a method for preparing a catalyst for photocatalytic oxidation of polystyrene foam plastics into benzoic acid, the conditions and steps are as follows:

[0006] (1) Preparation of Pt / TiO2 catalyst. 90 mL of distilled water and 10 mL of anhydrous ethanol were weighed and placed in a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 2.724-8.173 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min. Then, it was vigorously stirred for 10 min in a dark 25°C water bath, and then stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A). The liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground. The obtained sample was (a) Pt / TiO2 (mass fraction of a-Pt) catalyst.

[0007] (2) Preparation of Pt-Au / TiO2 catalyst. Measure 90 mL of distilled water and 10 mL of anhydrous ethanol and put them into a beaker. Then slowly add 0.2000 g (a) of Pt / TiO2 catalyst and 1.069-4.276 mL HAuCl4·3H2O (1 mg / mL) solution was stirred evenly, and the suspension was ultrasonically treated for 10 minutes; then it was vigorously stirred for 10 minutes in a dark 25°C water bath, and then continued to stir for 40 minutes under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 19A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 hours and then ground to obtain (a) Pt-(b) Au / TiO2 (b-mass fraction of Au) catalyst; the (a) Pt-(b) Au / TiO2 catalyst was placed in a tubular furnace and calcined at 400-600°C for 1-3 hours to obtain (a) Pt-(b) Au / TiO2-XY (X-calcination temperature, Y-calcination time, unit is h) catalyst.

[0008] The present invention provides an application of a catalyst for photocatalytic oxidation of polystyrene foam plastics into benzoic acid, and the conditions and steps are as follows:

[0009] 30-50 mg of catalyst, 6 mL of ethyl acetate and 10.4 mg of polystyrene foam plastic are respectively added to a quartz glass reactor, a certain amount of oxygen is filled into the reactor after the reactor is sealed, and after stirring for 30 minutes in the dark, the reactor is kept warm with 43-53° C. circulating water, and the reaction is stirred for 0.5-5 hours under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 16 A); after the reaction is completed, excessive ethanol is added to the reactor to precipitate unreacted polystyrene foam plastic, and then the liquid and solid are separated by centrifugation; the liquid is transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard is added, and the volume is fixed with anhydrous ethanol, the liquid is analyzed by gas chromatography, and the yield of benzoic acid is calculated by the internal standard method.

[0010] The beneficial effects of the present invention are as follows: the catalyst raw material is easily available, non-toxic and harmless, the synthesis method is simple and easy, and environmentally friendly, and it is used for photocatalytic oxidation of polystyrene foam plastics into benzoic acid. The reaction conditions are mild, the energy consumption is low, and it is environmentally friendly. The hydrocarbon resources in polystyrene can be converted into high-value-added benzoic acid with a high yield. DETAILED DESCRIPTION

[0011] Example 1

[0012] 40 mg of rutile TiO2 nanoparticles, 6 mL of ethyl acetate, and 10.4 mg of polystyrene foam were added to a quartz glass reactor respectively. A certain amount of oxygen was introduced into the reactor after the reactor was sealed. After stirring for 30 min in the dark, the reactor was kept warm with 48°C circulating water, and the reaction was stirred for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 16 A). After the reaction was completed, excess ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and the solid were separated by centrifugation. The liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol. The liquid was analyzed by gas chromatography, and the yield of benzoic acid was calculated to be 3.38% by the internal standard method.

[0013] Example 2

[0014] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground. The obtained sample was a (0.8%) Pt / TiO2 catalyst, and then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt / TiO2-500-2 catalyst; 40 mg (0.8%) and 1.5 mg (0.8%) Pt / TiO2-500-2 were added to a quartz glass reactor. Pt / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 minutes, use 48°C circulating water to keep the reactor warm, and stir the reaction for 5 hours under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL of o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 9.26%.

[0015] Example 3

[0016] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample (0.5%) Au / TiO2 catalyst, which was then calcined at 500°C for 2 h in a tube furnace to obtain a (0.5%) Au / TiO2-500-2 catalyst; 40 mg (0.5%) A u / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 minutes, use 48°C circulating water to keep the reactor warm, and stir the reaction for 5 hours under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL of o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 7.31%.

[0017] Example 4

[0018] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and the solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 14.75%.

[0019] Example 5

[0020] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 2.724 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground. The obtained sample was a (0.5%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.5%) Pt / TiO2 catalyst and 2.105 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.5%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.5%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0 .5%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and the yield of benzoic acid calculated by the internal standard method is 7.57%.

[0021] Example 6

[0022] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 8.173 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground. The obtained sample was a (1.5%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (1.5%) Pt / TiO2 catalyst and 2.105 mL of H2PtCl6·6H2O solution were slowly added. HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (1.5%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (1.5%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (1. 5%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 16.56%.

[0023] Example 7

[0024] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 1.052 mL of H2PtCl6·6H2O solution were slowly added. HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.25%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.25%) Au / TiO2-500-2 catalyst; 40 mg (0 .8%) Pt-(0.25%) Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48°C circulating water, and stir the reaction for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and the yield of benzoic acid calculated by the internal standard method is 9.81%.

[0025] Example 8

[0026] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a (0.8%) Pt / TiO2 catalyst sample; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 4.210 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(1%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(1%) Au / TiO2-500-2 catalyst; 40 mg (0.8 %)Pt-(1%)Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48℃ circulating water, and stir the reactor for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and the yield of benzoic acid calculated by the internal standard method is 10.74%.

[0027] Example 9

[0028] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst; 40 mg (0.8%) Pt-(0.5%) Au / TiO2 catalyst was added to a quartz glass reactor, respectively. agent, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48℃ circulating water, and stir the reaction for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and the solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and the yield of benzoic acid calculated by the internal standard method is 7.62%.

[0029] Example 10

[0030] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined in a tube furnace at 400°C for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-400-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-400-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam, sealed the reactor, filled with a certain amount of oxygen, stirred in the dark for 30 min, kept the reactor warm with 48°C circulating water, and stirred for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction was completed, excessive ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and the solid were separated by centrifugation; the liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol, the liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 10.00%.

[0031] Embodiment 11

[0032] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 600°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-600-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-600-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 14.15%.

[0033] Example 12

[0034] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to be stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 1 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-1 catalyst; 40 mg (0 .8%) Pt-(0.5%) Au / TiO2-500-1 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastics were added to the reaction kettle, a certain amount of oxygen was introduced into the sealed reaction kettle, and after stirring for 30min in the dark, the reaction kettle was kept warm with 48°C circulating water, and the reaction was stirred for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction was completed, excess ethanol was added to the reaction kettle to precipitate the unreacted polystyrene foam plastics, and then the liquid and the solid were separated by centrifugation; the liquid was transferred to a 50mL volumetric flask, 10μL o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol, and the liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 9.39%.

[0035] Embodiment 13

[0036] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 3 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-3 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-3 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, sealed the reactor and filled with a certain amount of oxygen, stirred in the dark for 30 min, then kept warm with 48°C circulating water, stirred and reacted for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction was completed, excessive ethanol was added to the reactor to precipitate the unreacted polystyrene foam plastic, and then the liquid and solid were separated by centrifugation; the liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol, the liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 14.38%.

[0037] Embodiment 14

[0038] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 30 mg (0 .8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and the solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 8.74%.

[0039] Embodiment 15

[0040] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 50 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 48°C circulating water, and stir the reactor for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 15.41%.

[0041] Example 16

[0042] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam, sealed the reactor, filled with a certain amount of oxygen, stirred in the dark for 30 min, kept the reactor warm with 48°C circulating water, and stirred for 0.5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction was completed, excessive ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and solid were separated by centrifugation; the liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol, the liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 0.49%.

[0043] Embodiment 17

[0044] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0 .8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 48°C circulating water, and stir the reactor for 2h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 5.47%.

[0045] Embodiment 18

[0046] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 48°C circulating water, and stir the reactor for 8 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up the volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 18.45%.

[0047] Embodiment 19

[0048] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0 .8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6mL ethyl acetate, 10.4mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30min, keep the reactor warm with 38°C circulating water, and stir the reaction for 5h under the irradiation of a xenon lamp (300W, mixed light with a wavelength of 300-2500nm, current 16A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50mL volumetric flask, add 10μL o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and the yield of benzoic acid calculated by the internal standard method is 9.17%.

[0049] Embodiment 20

[0050] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, sealed the reactor and filled with a certain amount of oxygen, stirred in the dark for 30 min, then kept warm with 43°C circulating water, stirred and reacted for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction was completed, excessive ethanol was added to the reactor to precipitate the unreacted polystyrene foam plastic, and then the liquid and solid were separated by centrifugation; the liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol, the liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 12.39%.

[0051] Embodiment 21

[0052] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined at 500°C in a tube furnace for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; 40 mg (0. 8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate, 10.4 mg polystyrene foam plastic, seal the reactor and fill it with a certain amount of oxygen, stir in the dark for 30 min, keep the reactor warm with 53°C circulating water, and stir the reaction for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A); after the reaction is completed, add excess ethanol to the reactor to precipitate the unreacted polystyrene foam plastic, and then centrifuge to separate the liquid and solid; transfer the liquid to a 50 mL volumetric flask, add 10 μL of o-dichlorobenzene internal standard, and then make up to volume with anhydrous ethanol, analyze the liquid by gas chromatography, and calculate the yield of benzoic acid by the internal standard method to be 18.42%.

[0053] Embodiment 22

[0054] 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) were slowly added. After stirring evenly, the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol were measured and put into a beaker, and then 0.2000 g of (0.8%) Pt / TiO2 catalyst and 2.105 mL of HAuCl4·3H2O solution (1 mg / mL) was stirred evenly, and the suspension was ultrasonically treated for 10 min; then it was vigorously stirred in a dark 25°C water bath for 10 min, and then it was continuously stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 19 A) light source; the liquid-solid mixture was separated by suction filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h and then ground to obtain a sample of (0.8%) Pt-(0.5%) Au / TiO2 catalyst, which was then calcined in a tube furnace at 500°C for 2 h to obtain a (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst; in a stone 40 mg (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate and 10.4 mg polystyrene foam were added to a quartz glass reactor respectively. After the reactor was sealed, a certain amount of oxygen was introduced. After stirring for 30 min in the dark, the reactor was kept warm with 53°C circulating water and stirred for 5 h in the dark. After the reaction was completed, excess ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and solid were separated by centrifugation. The liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol. The liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 0.15%.

[0055] Embodiment 23

[0056] 6 mL of ethyl acetate and 10.4 mg of polystyrene foam were added to a quartz glass reactor respectively, and a certain amount of oxygen was introduced into the reactor after the reactor was sealed. After stirring for 30 min in the dark, the reactor was kept warm with 53° C. circulating water, and stirred for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 16 A). After the reaction was completed, excess ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and the solid were separated by centrifugation. The liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol. The liquid was analyzed by gas chromatography, and the yield of benzoic acid calculated by the internal standard method was 0.91%.

Claims

1. A (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst for photocatalytic oxidation of polystyrene foam plastics into benzoic acid, characterized in that: 40 mg (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst, 6 mL ethyl acetate and 10.4 mg polystyrene foam were added to a quartz glass reactor, and a certain amount of oxygen was introduced into the reactor after it was sealed. After stirring in the dark for 30 min, the reactor was kept warm with 53°C circulating water, and stirred for 5 h under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, current 16 A). After the reaction, excess ethanol was added to the reactor to precipitate the unreacted polystyrene foam, and then the liquid and solid were separated by centrifugation. The liquid was transferred to a 50 mL volumetric flask, 10 μL of o-dichlorobenzene internal standard was added, and the volume was fixed with anhydrous ethanol. The liquid was analyzed by gas chromatography, and the yield of benzoic acid was calculated to be 18.42% by the internal standard method. The preparation method of the (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst is as follows: 90 mL of distilled water and 10 mL of anhydrous ethanol are measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) are slowly added, and after stirring evenly, the suspension is ultrasonically treated for 10 min, and then vigorously stirred for 10 min in a dark 25°C water bath, and then stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 19 A), and the liquid-solid mixture is separated by filtration, and the obtained solid is washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a sample of (0.8%) Pt / TiO2 catalyst; 90 mL of distilled water and 10 mL of anhydrous ethanol are measured and put into a beaker, and then 0.2000 g of anatase TiO2 nanoparticles and 4.359 mL of H2PtCl6·6H2O solution (1 mg / mL) are slowly added, and after stirring evenly, the suspension is ultrasonically treated for 10 min, and then vigorously stirred in a dark 25°C water bath for 10 min, and then stirred for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 19 A). (0.8%) Pt / TiO2 catalyst and 2.105 mL HAuCl4·3H2O solution (1 mg / mL) were mixed and stirred evenly, and the suspension was ultrasonically treated for 10 min, then vigorously stirred for 10 min in a dark 25°C water bath, and then continued to stir for 40 min under the irradiation of a xenon lamp (300 W, mixed light with a wavelength of 300-2500 nm, and a current of 19 A). The liquid-solid mixture was separated by filtration, and the obtained solid was washed with ultrapure water, dried at 80°C for 12 h, and then ground to obtain a (0.8%) Pt-(0.5%) Au / TiO2 catalyst; and then calcined at 500°C in a tubular furnace for 2 h to obtain the (0.8%) Pt-(0.5%) Au / TiO2-500-2 catalyst.

Citation Information

Patent Citations

  • Method for preparing single aromatic ring chemical raw material through thermal cracking of waste polystyrene

    CN117185890A